Real Effects of International Tax Planning: Evidence from Domestic Acquisitions - CHOW, Travis (Institutional Knowledge at Singapore Management University, 2014)
We examine whether and how the tax haven subsidiary profiles of U.S. acquirers and targets affect M&A pairing. Using disclosed material subsidiary data, we develop two measures of tax haven subsidiary relatedness between the acquirer and its target. Examining the associations of these measures with the probability of merger pair formation, the results suggest that acquirers are more likely to select targets whose subsidiaries are located in tax havens similar to their own, consistent with economies of scale in tax planning. This relation suggests that firms’ past tax planning decisions have significant effects on their future real corporate decisions.